Factors influencing properties of parallel laminated binderless bonded plywood manufactured from rotary cut birch (Betula pendula L.). (February 2014) - Ruponen, J.; Rautkari, L.; Belt, T.; Hughes, M.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, the moisture resistance properties of self-bonded plywood were enhanced by thermal modification. The plywood was prepared without any adhesive, using only heat, moisture and mechanical compression. It is known that self-bonded plywood or the wood welding joints suffer from delamination under moist conditions. The results show that the moisture resistance of the joints can be enhanced, i.e. the tendency of delamination can be reduced or eliminated (almost totally) by post-manufacture thermal modification. This was most probably caused by lowered water absorption, relaxation of stored strain energy and formation of crosslinks within the lignin–hemicellulose matrix. The changes in bond integrity in moist conditions as affected by different lay-up types and initial veneer moisture contents were also evaluated. Plywood from initially wet veneers was found to have greater bond stability when soaked. This might be caused by increased crosslinks, because the lignin–hemicellulose matrix is more mobile in wet conditions.